(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. Apatite-related modified calcium phosphates have increasing interest for use in orthopedics as bone substitutes. In addition, partial substitution of phosphate by vanadate-group in the anionic sublattice opens up wide opportunities in the development of catalysts for organic synthesis, as well as materials with special optical properties. The aim of the work are the synthesis of apatite-related calcium phosphate-vanadates and the study of the effect of partial substitution of phosphate by the vanadate-anion in the structure and the sorption of zinc cations from an aqueous solution on the band gap of materials. Methods. The samples were synthesized from aqueous solutions of the system NH4+-Сa2+-PO43–NO3–VO43- with molar ratios Сa2+:PO43-:-VO43- = 10: (6-х): х, heated to 500°С and used for sorption of Zn2+ cations from the aqueous solution with subsequent heating to 500°С for 2 hours. The methods of powder X-ray diffraction, FTIR and electron spectroscopy were used for their characterization. Results. According to the X-ray diffraction data, the synthesized samples are monophasic and belong to the hexagonal system, space group P63/m (apatite-type structure), and the calculated parameters of the lattice increase as the vanadate content in their composition increases. FTIR spectroscopy data confirm the presence of two types of anions (РО4 and VO4) in the composition of the synthesized phases. A decrease in the band gap width was established as the degree of substitution of phosphate anion by vanadate increased to 50%, as well as upon sorption of Zn2+ cations onto the surface of synthesized nanoparticles of vanadate-containing hydroxyapatites and their heating to 500°С. Сonclusions. The obtained results can be used in the future in the development of materials with special optical properties or catalysts for organic transformations based on apatite-related calcium phosphate-vanadates.